2001
DOI: 10.1021/jp011722v
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Tuning of Photoactive Yellow Protein. Theoretical and Experimental Analysis of Medium Effects on the Absorption Spectrum of the Chromophore

Abstract: We apply a SCRF-PCM-CI calculation to elucidate the mechanism of spectral tuning in photoactive yellow protein (PYP). It is shown that the calculation well reproduces solvatochromic shifts observed for some model compounds of the PYP chromophore. By regression analysis, we obtain an empirical equation to predict solvatochromic shifts of these compounds for a given set of dielectric constant and refractive index. Next, using a classical electrostatic theory and the crystal structure of PYP, the value of refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…Also, hydrogen bonding by water to the proximal carbonyl oxygen, which is solventaccessible in Ppr-PYP (see above), could also contribute to a blue shift in absorption because of resonance stabilization between quinonic and phenolic forms of the chromophore (19). However, it is difficult to correlate the structural changes observed in this structure with the specific and nonspecific protein environmental effects that affect chromophore absorption in PYPs (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…Also, hydrogen bonding by water to the proximal carbonyl oxygen, which is solventaccessible in Ppr-PYP (see above), could also contribute to a blue shift in absorption because of resonance stabilization between quinonic and phenolic forms of the chromophore (19). However, it is difficult to correlate the structural changes observed in this structure with the specific and nonspecific protein environmental effects that affect chromophore absorption in PYPs (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…Substitution mutations at the residue under study in principle can affect three independent properties of the S 0 and S 1 energy surfaces: ΔE, R e , and W. The expected consequences of changes in these three properties can be formulated as described below. The electronic structure of PYP has been examined by a number of computational studies (24)(25)(26)(27), but the details of the shape of the S 0 and S 1 energy surfaces and Franck-Condon factors for the pCA in its active site are difficult to obtain with high accuracy. However, general trends in changes in the position and shape of the absorbance and emission fluorescence maxima as a result of changes in ΔE, R e , and W can be derived.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and computational work on PYP has confirmed that the chromophore absorbance band at 446 nm is a π-π Ã transition, has identified Glu46 and Tyr42 as the main contributors to the effect of the protein on the pCA absorbance spectrum, and has revealed that the hydrogen bonding interactions between these two side chains and the pCA are critical for spectral tuning in PYP (18)(19)(20)(21)(24)(25)(26)(27). These studies have all focused on the energy gap between the S 0 and S 1 states, i.e., ΔE-tuning.…”
Section: Correlating Fluorescence Quantum Yield and Excited State Lifmentioning
confidence: 99%
See 2 more Smart Citations